Pengembangan Multimedia Interaktif Sebagai Alat Diseminasi Program Balai Diklat Industri Padang - Ilham, Muhammad Rizkho; Bentri, Alwen; Novrianti, Novrianti; Anugrah, Septriyan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by the need for the Padang Industrial Training Center (BDI Padang) to increase the ease of disseminating information regarding the 3 in 1 training program. BDI Padang, as part of the Indonesian Ministry of Industry, has an important task in organizing competency-based training. This interactive multimedia development aims to provide a dynamic and interactive platform so that information can be conveyed in an interesting and easy to understand manner by stakeholders. This research uses the research and development (R&D) method with the 4D development model (Define, Design, Develop, & Disseminate). At the testing stage, the validity of the multimedia product is tested by two media validators and one material validator. Media validation resulted in an average score of 3.84 from validator I and 4.00 from validator II, while material validation obtained a score of 3.92, both of which fall into the